Hungarian Nationalism and the Origins of Neolog Judaism - Rethelyi, Mari (2014)
The new religious movement of the Neolog Jews in Hungary argued for Jews’ acceptance into Hungarian society by articulating an ethnic identity compatible with that of Hungarians. Neolog Jews promoted nationalism by propagating an ethnic Oriental Jewish identity mirroring Hungarian nationalist identity. By negotiating a common identity, Neolog Jews hoped to achieve recognition as fellow Hungarians. The history of the Neologs is unique because a non-Semitic, ethno-nationalist definition of Jewish identity occurred only in Hungary. Neolog Judaism constitutes a significant religious group not only because of its isolated case of nationalist ethnic formation of Jewish identity, but also because it became the mainstream Jewish religious movement in Hungary.
Keywords: Gog-Magog; minority history; Oriental Studies; Reform Judaism; Rabbinical Seminary; Identity; Khazar; Hungarian Jews; Hungary; Neolog Judaism